2016
DOI: 10.1177/0972150916630447
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Malaysian Consumers’ Channel-switching Intention: Using theory of Planned Behaviour

Abstract: The purpose of the current study is to examine the effect of behavioural attitude, subjective norm (SN) and perceived behavioural control (PBC) on channel-switching intention in regards to Internet and brick-and-mortar stores channels in Malaysia. Theory of planned behaviour (TPB) was used in this study. Partial least squares (PLS) based on the structural equation modelling (SEM) technique was used to analyze the data. The study was based on the simple random sampling, with the survey instrument administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 133 publications
(253 reference statements)
4
20
1
2
Order By: Relevance
“…Further, we found that consumers’ attitudes and subjective norms about switching channels to online stores during COVID-19 had positive effects on their behavioral intentions to switch to the online channel, while behavioral control had no effect on the intention to do so. Previous researchers have supported the results that attitudes and subjective norms had positive effects on the intention to switch to online shopping channels, while perceived behavioral control had no influence on this intention (Madahi & Sukati, 2016). Because shopping for fashion products online is already popular among most consumers, their perceptions of their ability to adopt online stores might have weaker effects on future shopping channel choices.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Further, we found that consumers’ attitudes and subjective norms about switching channels to online stores during COVID-19 had positive effects on their behavioral intentions to switch to the online channel, while behavioral control had no effect on the intention to do so. Previous researchers have supported the results that attitudes and subjective norms had positive effects on the intention to switch to online shopping channels, while perceived behavioral control had no influence on this intention (Madahi & Sukati, 2016). Because shopping for fashion products online is already popular among most consumers, their perceptions of their ability to adopt online stores might have weaker effects on future shopping channel choices.…”
Section: Discussionmentioning
confidence: 69%
“…Further, when consumers are confident about their ability to adopt a new action (i.e., online shopping) and believe it would save costs, the belief increases their perceived behavior control (Madahi & Sukati, 2016). Thakur (2018) found that when consumers were more confident about their ability (i.e., self-efficacy) and believed the app would help them make correct decisions (i.e., response efficacy), they were more likely to adopt the app to purchase fashion products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, it is expected that consumer attitude towards mobile marketing is highly dependent upon the attitudes held towards advertising in general. According to a study by Madahi and Sukati (2016), Malaysian consumers change channels from the Internet to brick-and-mortar stores, and vice versa, when a channel is not favourable. The results from these studies confirm the role that attitudes play towards the intention behind consumer channel-switching, and with regard to both the channels.…”
Section: Consumer Attitude Towards Mobile Advertisingmentioning
confidence: 99%
“…Vários autores têm vindo, desde a formulação da teoria e até aos dias de hoje, a aplicar os modelos de ação refletida e planeada a um vasto leque de intenções e comportamentos: comportamentos sexuais de risco (Albarracín, Johnson, Fishbein, & Muellerleile, 2001;Godin & Kok, 1996), o uso do preservativo (Davis et al, 2016;Malcolm et al, 2013), comportamentos preventivos do cancro de pele (Figueiras, Alves, & Borracho, 2004), a discriminação sexual positiva no trabalho (Snyder & Swann, 1976), escolha de voto nas eleições presidenciais (Fishbein & Ajzen, 1981;Watters, 1989), escolha do método de alimentação do bebé pela mãe (Manstead, Proffitt, & Smart, 1983), consumo excessivo de álcool (Schlegel, d'Avernas, Zanna, DeCourville, & Manske, 1992), a intenção dos consumidores de mudar de canal (Madahi & Sukati, 2016), a participação em eventos profissionais de futebol (Eddosary, Ko, Sagas, & Kim, 2015), a compra local de comida (Shin, Hancer, & Song, 2016), o consumo do tabaco entre estudantes (Su et al, 2015), a adoção de comportamentos de risco durante a condução (Lee, Geiger-Brown, & Beck, 2016;Li, Shi, Liu, & Wang, 2016;Rowe et al, 2016), a intenção dos adolescentes se voluntariarem (Reuveni & Werner, 2015), a tomada de decisões éticas nas redes sociais (e.g., face ao cyberbullying) (Jafarkarimi, Saadatdoost, Sim, & Hee, 2016), comportamentos de risco online (Sasson & Mesch, 2016), a intenção de seguir marcas no Twitter (Chu, Chen, & Sung, 2016), a compra de viagens online (Amaro & Duarte, 2016), a adoção de comportamentos pró-ambiente (Botetzagias, Dima, & Malesios, 2015;Chung, 2016;Masud et al, 2016), a prática de exercício físico (Wigginton, Lee, Marshak, & Freier, 2016), a utilização de métodos de educação inclusivos (Yan & Sin, 2015), a prática de hábitos de alimentação saudável …”
Section: A Teoria Da Ação Planeadaunclassified